Kombinasi Delphi XE8 dan Ms Access dalam Desain Aplikasi DASS - Syaharuddin Syaharuddin; Evi Febriana; Vera Mandailina (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
This study aims to develop Delphi XE8 software combined with Microsoft Access into a new application of the type of Setup Compiler called DASS. This application development uses 4-D development methods (Define, Design, Develop, and Disseminate). This application was developed based on Setup Compiler is an application with a small memory and easy in the process of deployment and is designed with two types of files Installer and Portable so easy in the distribution of files to users, especially students and lecturers. Validator gives an average response of 4.28 which means